Development of nano-satellite communications subsystem (part 1 - hardware) - Lim, Justin Wei Qiang. (2011)
CubeSat is a project that was initiated by California Polytechnic State University (Cal Poly) and Stanford University to develop the specifications and standards to help universities worldwide to perform space science and exploration. It aims to provide students with hands on experience on designing the satellite and at the same time exposing them to the challenges of designing it. With that, Nanyang Technological University (NTU) hopes to provide its students with the same experience through VELOX-I, its first Nano-Satellite mission. This report presents a detailed illustration of the designing the hardware portion of the communication subsystem for the Nano-Satellite project. It consists of two parts; the link budget and the designing of the In-House communication subsystem.